SETS-Based Physics Learning Workshop: Strengthening Teachers’ Role in Fostering Students’ Scientific Literacy - Abdul Salam M; Mustika Wati; Sri Hartini; Sarah Miriam; Dewi Dewantara; Surya Haryandi; Isnaini Agus Setiono; Siti Marlina; Rahmah Andriani (Borneo Research and Education Center, 2025)
The Physics Learning Workshop based on Science, Environment, Technology, and Society (SETS) was carried out to enhance the ability of physics teachers in the MGMP of Hulu Sungai Selatan Regency to foster students’ scientific literacy. The background of this activity is the low achievement of Indonesian students’ scientific literacy as reported by PISA, as well as the tendency of physics learning in schools to focus heavily on memorizing formulas and practicing problems, which makes it less relevant to real-life contexts. Partner teachers also experienced difficulties in designing contextual teaching materials, making an assistance program through an applied workshop necessary. The workshop was conducted in five stages: socialization, training, technology implementation, mentoring and evaluation, and program sustainability. The training materials included strengthening the concept of scientific literacy, introducing the SETS approach, and practicing the development of contextual SETS-based physics teaching modules. Teachers not only received material but were also guided in designing teaching tools that engage students in linking physics concepts with real phenomena in their environment, including local issues such as annual floods and wetland utilization. The evaluation results showed an improvement in teachers’ skills in designing and implementing SETS-based learning that encourages students to be more active, critical, and reflective in understanding physics concepts. More than 80% of teachers expressed satisfaction with the activity, while the implementation of learning practices reached the “good” category. This workshop successfully strengthened the role of teachers as facilitators who are able to cultivate students’ scientific literacy through contextual, innovative, and relevant physics learning in daily life.